2014
DOI: 10.1111/gcb.12608
|View full text |Cite
|
Sign up to set email alerts
|

Afforestation effects on SOC in former cropland: oak and spruce chronosequences resampled after 13 years

Abstract: Chronosequences are commonly used to assess soil organic carbon (SOC) sequestration after land-use change, but SOC dynamics predicted by this space-for-time substitution approach have rarely been validated by resampling. We conducted a combined chronosequence/resampling study in a former cropland area (Vestskoven) afforested with oak (Quercus robur) and Norway spruce (Picea abies) over the past 40 years. The aims of this study were (i) to compare present and previous chronosequence trends in forest floor and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 55 publications
4
19
0
Order By: Relevance
“…On the contrary, decreased C density/CSP resulting from the five restoration practices associated with conversions from croplands back to grasslands or shrublands was similar to the results of a resampling study and meta‐analysis, which revealed that afforestation in former croplands can decrease SOC stocks (Bárcena et al. , Fujisaki et al. ), probably due to the accelerated decomposition of SOC caused by fresh C inputs (Fontaine et al.…”
Section: Discussionsupporting
confidence: 68%
“…On the contrary, decreased C density/CSP resulting from the five restoration practices associated with conversions from croplands back to grasslands or shrublands was similar to the results of a resampling study and meta‐analysis, which revealed that afforestation in former croplands can decrease SOC stocks (Bárcena et al. , Fujisaki et al. ), probably due to the accelerated decomposition of SOC caused by fresh C inputs (Fontaine et al.…”
Section: Discussionsupporting
confidence: 68%
“…The results indicate that afforestation by mountain birch, and the establishment of birch woodlands, can increase the bulk SOC stock (0-30 cm), which is in accordance with the findings of Bárcena et al, (2014). They are, however, contrary to the results of Ritter (2007), who studied afforestation on heathland.…”
Section: Studying the Usually Tested Bulk Soc Stockssupporting
confidence: 85%
“…It was noted that soil organic carbon sequestration increases with the planting age (Berthrong et al, 2012;Boussougou et al, 2010;Jiao et al, 2011). Coincidently, it has been observed that soil carbon loss may occur in the first decades after planting of tree species and is followed by a recovery stage of unknown duration (Bárcena et al, 2014). It was found that the carbon sequestration value is largely determined by the species composition within tree plantations (Gurmesa et al, 2013).…”
Section: Introductionmentioning
confidence: 98%